A method for preparing a nickel-based self-supporting water electrolysis hydrogen evolution catalyst

CN117626319BActive Publication Date: 2026-10-30HENAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311601512.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-10-30
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

而大部分NF或镍网基自支撑催化电极材料析氢耐久性一般的原因之一可能是商用NF或镍网基体的“大孔径、小骨架”结构,一方面“大孔径”易导致析氢反应中生成气体的聚积,大尺寸气泡对催化相表面剧烈冲击使其开裂或剥落,造成失效;另一方面纤细的“小骨架”电阻大,单位面积的催化相负载量低,且难以为催化相的附着提供足够牢固且稳定的原位自生位点,导致基体与催化相之间的结合强度不高

Benefits of technology

(1)本发明的制备工艺采用粉末冶金+水热合成的组合方法,在烧结态多孔镍基体上原位自生出同源催化相,相较于现有的泡沫镍、镍网等传统多孔镍基体,具有导电性好、与催化相的结合强度高、力学性能好等突出优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117626319B_ABST
    Figure CN117626319B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a nickel-based self-supporting water electrolysis hydrogen evolution catalyst, which adopts a combination method of powder metallurgy and hydrothermal synthesis, a graphite mold loaded with nickel powder is placed into an SPS furnace for sintering, a porous nickel matrix is obtained after sintering, the porous nickel matrix is subjected to a hydrothermal reaction with a sodium selenite solution, and after the reaction is completed, washing and drying are carried out, and finally the nickel-based self-supporting water electrolysis hydrogen evolution catalyst is obtained. The nickel-based self-supporting water electrolysis hydrogen evolution catalyst prepared by the method has the characteristics of high catalytic hydrogen production activity, long service life and easy processing. The nickel-based self-supporting water electrolysis hydrogen evolution catalyst prepared by taking the sintered porous nickel metal as a matrix can be directly embedded on a steel plate and applied to an existing electrolytic tank equipment as an electrode plate material, so that the technical problem that the catalytic activity and durability of the key electrode material of the existing alkaline water electrolytic tank are difficult to be considered together can be solved, and the nickel-based self-supporting water electrolysis hydrogen evolution catalyst has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic material preparation technology, specifically to a method for preparing a nickel-based self-supporting electrolytic water electrolysis hydrogen evolution catalyst, which belongs to a technical application of the synergistic preparation of catalytic materials by powder metallurgy and wet chemical methods. Background Technology

[0002] Hydrogen energy is considered one of the most promising clean energy sources and has attracted much attention. According to the "Medium and Long-Term Plan for the Development of the Hydrogen Energy Industry (2021-2035)" issued by the state, the proportion of hydrogen production from renewable energy sources will be gradually increased to support the green transformation and development of energy. Water electrolysis is a typical renewable energy hydrogen production process. This technology consists of two half-reactions: the cathode hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction (OER). Due to the electrolyte resistance and internal resistance of the electronic circuit in the hydrogen and oxygen generation reaction, a highly efficient electrocatalyst is needed to reduce the overpotential of the reaction kinetics and improve hydrogen production efficiency. While noble metal materials (such as Pt) exhibit excellent catalytic performance, they are expensive. Research has found that relatively inexpensive transition metal selenides (TMSes) have attracted attention due to their good catalytic activity.

[0003] However, most TMSes materials are typically in fine powder form, making them difficult to bond with current collectors during application. This results in high interfacial resistance and weak bonding with the matrix, further contributing to the short lifespan of the catalytic electrode materials. In-situ self-generating TMSes catalysts from the matrix is ​​an effective approach. In recent years, nickel foam (NF) or nickel mesh has been commonly used domestically and internationally as the matrix to in-situ support various catalytic phase compounds, which has promoted the research of Ni-based self-supporting catalytic electrode materials to some extent.

[0004] Despite significant progress in the research of preparing Ni-based self-supporting catalytic materials using NF or nickel mesh as matrix materials, their industrial applications remain challenging. A review of domestic and international literature reveals that only a very small number of NF or nickel mesh-based self-supporting catalytic electrode materials can achieve hydrogen evolution exceeding 200 hours in a single long-term cycle at a stable current density or potential. Therefore, in the design of industrial alkaline water electrolyzers, most companies prefer to use pure metallic NF or nickel mesh materials with moderate catalytic activity but durable service, rather than investing in further surface functionalization. One reason for the generally poor hydrogen evolution durability of most NF or nickel mesh-based self-supporting catalytic electrode materials may be the "large pore size, small framework" structure of commercially available NF or nickel mesh matrices. On the one hand, the "large pore size" easily leads to the accumulation of gas generated during the hydrogen evolution reaction; large bubbles violently impact the catalytic phase surface, causing cracking or peeling, resulting in failure. On the other hand, the slender "small framework" has high resistance, low catalytic phase loading per unit area, and difficulty in providing sufficiently strong and stable in-situ self-generated sites for catalytic phase adhesion, resulting in low bonding strength between the matrix and the catalytic phase. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a method for preparing a nickel-based self-supporting electrolytic hydrogen evolution catalyst for water electrolysis. This method is simple in steps, low in raw material cost, and controllable in process. The resulting electrode exhibits both stable catalytic activity and long-term durability, meeting the objective requirements of industrial water electrolysis hydrogen evolution equipment for long-term and high-efficiency catalytic materials, and is expected to achieve large-scale production.

[0006] To achieve the above objectives, this invention discloses a method for preparing a nickel-based self-supporting hydrogen evolution catalyst for water electrolysis, comprising the following steps: (1) Weigh a certain amount of nickel powder and select a graphite mold of appropriate size according to the size of the final product.

[0007] For example, the diameter and thickness of the final product are determined based on its volume, and a graphite mold with a suitable inner diameter is selected accordingly. The mass of nickel powder required is estimated by multiplying the volume and density.

[0008] The graphite mold used includes a graphite conical mandrel, a graphite sleeve, a graphite pressure bar, and a graphite gasket.

[0009] The nickel powder particles have a particle size of 100~300 mesh.

[0010] (2) Fill the graphite mold with nickel powder and place a graphite pad at the top and bottom of the graphite sleeve (between the graphite sleeve and the conical top).

[0011] The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve, but smaller than the outer diameter of the graphite sleeve.

[0012] The purpose of adding graphite gaskets here is to increase the current flow cross-sectional area of ​​the copper electrodes at both ends of the SPS furnace, reduce resistance, increase current, promote the heating of the graphite mold containing nickel powder, and use instantaneous thermal effect to sinter and solidify the nickel powder inside.

[0013] (3) The graphite mold is placed in a spark plasma sintering furnace (SPS) for sintering. After sintering, it is cooled to room temperature and removed to obtain a porous nickel matrix.

[0014] The SPS furnace sintering temperature selected here is 600℃~1200℃, the heating rate is 50~100℃ / min, and the sintering holding time is 2min. The temperature and heating rate need to be strictly controlled. If the temperature is too low, the formability will be poor and it will be easy to pulverize. If the temperature is too high, the formed sample will have high density, no porous structure on the surface, and small specific surface area, which is not conducive to the adhesion and function of the catalyst. Similarly, the heating rate also affects the size of the product pores.

[0015] (4) Weigh a certain amount of sodium selenite (Na2SeO3) powder and dissolve it in distilled water. After stirring thoroughly, obtain solution A. Then transfer solution A together with the porous nickel matrix obtained in step (3) into the polytetrafluoroethylene liner of the stainless steel hydrothermal reactor, seal the hydrothermal reactor, and place it in a drying oven for hydrothermal reaction.

[0016] The amount of Na₂SeO₃ used here is 0.1~0.8 mmol, and the concentration of Na₂SeO₃ in solution A is 2~16 mmol / L. The amount and concentration of the raw materials need to be strictly controlled. If the concentration and amount are too low, the catalyst material will not adhere to the metal substrate surface; conversely, the catalyst material will accumulate and solidify on the metal substrate surface, which is not conducive to the efficient release of catalytic performance. Furthermore, the hydrothermal reaction temperature is 180~200℃, and the reaction time is 6~12 h. If the hydrothermal temperature is too low or the time is too short, the catalyst will not fully adhere and grow on the metal substrate surface; if the hydrothermal temperature is too high or the time is too long, it will lead to uneven catalyst morphology and reduce catalytic efficiency. (5) Take out the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then put it into a vacuum drying oven. After drying, the final product - nickel-based self-supporting electrolytic hydrogen evolution catalyst is obtained.

[0017] The drying temperature in the vacuum drying oven is 60-80℃, and the drying time is 12-24 hours. Rinsing with distilled water is mainly to remove residual sodium ions from the hydrothermal process, while rinsing with alcohol accelerates the removal of residual water molecules after the previous water wash and effectively disperses the formed particles. The drying temperature and time must be strictly controlled. If the temperature is too low, it will be difficult to remove deep-seated moisture between the particles; conversely, if the temperature is too high, it will easily cause oxidation of the particle surface, damaging the morphology of the catalyst adhering to the surface and hindering the effective performance of the catalytic reaction.

[0018] The present invention also discloses a nickel-based self-supporting electrolytic water hydrogen evolution catalyst prepared according to the above method, and the application of the nickel-based self-supporting electrolytic water hydrogen evolution catalyst in the electrolytic water hydrogen evolution reaction and oxygen evolution reaction under alkaline environment.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation process of the present invention adopts a combination of powder metallurgy and hydrothermal synthesis to generate a homologous catalytic phase in situ on the sintered porous nickel matrix. Compared with the existing traditional porous nickel matrix such as nickel foam and nickel mesh, it has outstanding advantages such as good conductivity, high bonding strength with the catalytic phase, and good mechanical properties.

[0020] (2) The nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared by the present invention has the characteristics of high catalytic hydrogen production activity, long service life and easy processing. The nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared with this sintered porous nickel metal as the matrix can also be directly embedded in the steel plate and used as the electrode plate material in the existing electrolytic cell equipment. It is expected to solve the technical problem that the catalytic activity and durability of the key electrode materials of the existing alkaline water electrolytic cell are difficult to balance, and has broad application prospects. Attached Figure Description

[0021] Figure 1 The diagram shows a comparison of the graphite molds used in the traditional SPS sintering process and the SPS sintering process of the present invention, where a is the graphite mold used in the traditional SPS sintering process and b is the graphite mold used in the SPS sintering process of the present invention. Figure 2 Photographs of the porous nickel matrix and nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared in Example 1; Figure 3 The XRD patterns of the porous nickel matrix and nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared in Example 2 are shown below. Figure 4 This is a SEM image of the nickel-based self-supporting hydrogen evolution catalyst for water electrolysis prepared in Example 2; Figure 5 This is a SEM image of the nickel-based self-supporting hydrogen evolution catalyst for water electrolysis prepared in Example 3; Figure 6 This is a comparison of the electrocatalytic water splitting performance of the Ni3Se2@Porous Ni self-supporting electrode and the Ni3Se2@NF self-supporting electrode prepared in Example 3.

[0022] Figure Labels 1-Graphite conical top, 2-Graphite sleeve, 3-Powder sample, 4-Graphite pressure bar, 5-Graphite gasket, 6-Copper electrode. Detailed Implementation

[0023] To better understand the content of this invention, it will be further described below with reference to specific embodiments and accompanying drawings. The following embodiments are based on the technology of this invention and provide detailed implementation methods and operating steps, but the scope of protection of this invention is not limited to the following embodiments.

[0024] A method for preparing a nickel-based self-supporting hydrogen evolution catalyst for water electrolysis mainly includes the following steps: (1) Weigh a certain amount of nickel powder and select a graphite mold of appropriate size according to the size of the final product.

[0025] For example, the diameter and thickness of the final product are determined based on its volume, and a suitable graphite mold is selected accordingly. The required mass of nickel powder is estimated by multiplying the volume and density.

[0026] The graphite mold used includes a graphite conical mandrel, a graphite sleeve, a graphite pressure bar, and a graphite gasket.

[0027] The nickel powder particles have a particle size of 100~300 mesh.

[0028] (2) Fill the graphite mold with nickel powder and place a graphite pad at the top and bottom of the graphite sleeve (between the graphite sleeve and the conical top).

[0029] The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve, but smaller than the outer diameter of the graphite sleeve.

[0030] The purpose of adding graphite gaskets here is to increase the current flow cross-sectional area of ​​the copper electrodes at both ends of the SPS furnace, reduce resistance, increase current, promote the heating of the graphite mold containing nickel powder, and use instantaneous thermal effect to sinter and solidify the nickel powder inside.

[0031] (3) The graphite mold is placed in an SPS furnace for sintering. After sintering, it is cooled to room temperature and removed to obtain a porous nickel matrix.

[0032] The selected SPS sintering temperature here is 600℃~1200℃, the heating rate is 50~100℃ / min, and the sintering holding time is 2min. Temperature and heating rate need to be strictly controlled. If the temperature is too low, the formability will be poor, and it will easily pulverize; if the temperature is too high, the formed sample will have high density, no porous structure on the surface, and a small specific surface area, which is not conducive to the adhesion and effectiveness of the catalyst. Similarly, the heating rate also affects the pore size of the product.

[0033] (4) Weigh a certain amount of sodium selenite (Na2SeO3) powder and dissolve it in distilled water. After stirring thoroughly, solution A is obtained. Then, solution A and the porous nickel matrix obtained in step (3) are transferred together to the polytetrafluoroethylene liner of the stainless steel hydrothermal reactor. The hydrothermal reactor is sealed and placed in a drying oven for hydrothermal reaction.

[0034] The amount of Na₂SeO₃ used here is 0.1~0.8 mmol, and the concentration of Na₂SeO₃ in solution A is 2~16 mmol / L. The amount and concentration of the raw materials need to be strictly controlled. If the concentration and amount are too small, the catalyst material will not adhere to the surface of the metal substrate; conversely, the catalyst material will accumulate and solidify on the surface of the metal substrate, which is not conducive to the efficient release of catalytic performance. Furthermore, the hydrothermal reaction temperature is 180~200℃, and the reaction time is 6~12 h. If the hydrothermal temperature is too low or the time is too short, the catalyst will not be able to fully adhere and grow on the surface of the metal substrate; if the hydrothermal temperature is too high or the time is too long, it will lead to uneven catalyst morphology and reduce catalytic efficiency.

[0035] (5) Take out the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then put it into a vacuum drying oven. After drying, the final product - nickel-based self-supporting electrolytic hydrogen evolution catalyst is obtained.

[0036] The drying oven temperature is 60~80℃, and the drying time is 12~24 hours. Rinsing with distilled water is mainly to remove residual sodium ions from the hydrothermal process, while rinsing with alcohol accelerates the removal of residual water molecules after the previous water wash and effectively disperses the formed particles. The drying temperature and time must be strictly controlled. If the temperature is too low, it will be difficult to remove deep-seated moisture between the particles; conversely, if the temperature is too high, it will easily cause oxidation of the particle surface, damaging the morphology of the catalyst adhering to the surface and hindering the effective performance of the catalytic reaction.

[0037] The present invention also discloses a nickel-based self-supporting electrolytic water hydrogen evolution catalyst prepared according to the above method, and the application of the nickel-based self-supporting electrolytic water hydrogen evolution catalyst in the electrolytic water hydrogen evolution reaction and oxygen evolution reaction under alkaline environment.

[0038] The features and reaction principle of this invention are as follows: The graphite mold used in the traditional SPS sintering process includes graphite conical tops 1 at the top and bottom, graphite pressure rods 4, and a graphite sleeve 2 in the middle, such as... Figure 1 As shown in a, the traditional SPS sintering process involves placing the powder sample 3 into a graphite sleeve 2, and sintering it using the pressure from the graphite conical head and graphite pressure rod, as well as the current drawn from the SPS copper electrode 6 (forming a circuit through the graphite conical head-graphite pressure rod-powder sample-graphite pressure rod-graphite conical head). In the SPS sintering process of this invention, two graphite pads 5 are placed sequentially at the upper and lower ends of the graphite sleeve using a graphite mold, as shown in the diagram. Figure 1As shown in b, this design, on the one hand, creates a circuit connection between the graphite conical tip and the graphite sleeve, increasing the cross-sectional area for current flow and generating a higher temperature environment around the powder sample; on the other hand, it reduces the pressure exerted on the powder sample by the SPS copper electrode. Benefiting from the higher temperature field and lower pressure, the powder sample easily forms a pore structure with "small pore size and large framework," thus creating a metal matrix suitable for in-situ growth of the catalytic phase. During the selenization process, a one-step hydrothermal process using sodium selenite is employed to precipitate a nano-sized nickel selenide catalytic layer in situ on the nickel metal matrix. This layer exhibits a uniform morphology, with vertically aligned nanosheets exposing more edge active sites, laying the foundation for improved catalytic performance.

[0039] This invention, through raw material control, mold improvement, sintering condition control, and hydrothermal condition control during the preparation process, results in a sintered porous nickel metal matrix with a porous and loose microstructure. This provides more sites for catalyst adhesion and significantly increases the contact area between the material and the electrolyte, allowing the catalytic reaction to proceed more fully. Furthermore, the water splitting products, hydrogen and oxygen, easily escape from the pores of the material, further optimizing the catalytic efficiency.

[0040] Example 1: (1) Weigh 3g of 300-mesh nickel powder and select a graphite mold with a diameter of φ20; (2) The nickel powder is loaded into the graphite mold, and a graphite gasket is placed at the upper and lower ends of the graphite sleeve (i.e., between the graphite sleeve and the conical top). The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve and smaller than the outer diameter of the graphite sleeve. (3) The graphite mold obtained in step (2) is placed in an SPS furnace for sintering. The sintering temperature is 600℃, the heating rate is 50℃ / min, and the sintering holding time is 2min. After sintering, the graphite mold is cooled to room temperature and removed to obtain a porous nickel matrix.

[0041] (4) Weigh 0.1 mmol of Na2SeO3 powder and dissolve it in 50 mL of distilled water. After stirring thoroughly, obtain solution A. Then, transfer solution A together with the porous nickel matrix obtained in step (3) into the polytetrafluoroethylene liner of a stainless steel hydrothermal reactor, seal the hydrothermal reactor, and place it in a drying oven for hydrothermal reaction. The hydrothermal reaction temperature is 180 °C, and the reaction time is 6 h.

[0042] (5) Remove the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then place it in a vacuum drying oven at 60°C for 12 hours. After drying, the final product - nickel-based self-supporting water electrolysis hydrogen evolution catalyst - is obtained.

[0043] The porous nickel matrix and nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared in this embodiment were macroscopically characterized, and the results are as follows: Figure 2 As shown, the part on the upper left of the ruler is a porous nickel matrix, and the part on the right is a nickel-based self-supporting electrolytic hydrogen evolution catalyst for water electrolysis. Figure 2 As can be seen, the porous nickel substrate prepared in this embodiment is a small gray disc with a diameter of 20 mm and a thickness of 2.1 mm, and multiple "small pits" are visible on its surface. After hydrothermal reaction, the final nickel-based self-supporting electrolytic hydrogen evolution catalyst has a black surface and a uniform color distribution.

[0044] Example 2: (1) Weigh 3g of 100-mesh nickel powder and select a graphite mold with a diameter of φ30; (2) The nickel powder is loaded into the graphite mold, and a graphite gasket is placed at the upper and lower ends of the graphite sleeve (i.e., between the graphite sleeve and the graphite conical top). The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve and smaller than the outer diameter of the graphite sleeve. (3) The graphite mold obtained in step (2) is placed in an SPS furnace for sintering. The sintering temperature is 1200℃, the heating rate is 100℃ / min, and the sintering holding time is 2min. After sintering, the graphite mold is cooled to room temperature and removed to obtain a porous nickel matrix.

[0045] (4) Weigh 0.6 mmol of Na2SeO3 powder and dissolve it in 50 mL of distilled water. After stirring thoroughly, obtain solution A. Then, transfer solution A together with the porous nickel matrix obtained in step (3) into the polytetrafluoroethylene liner of a stainless steel hydrothermal reactor, seal the hydrothermal reactor, and place it in a drying oven for hydrothermal reaction. The hydrothermal reaction temperature is 200 °C, and the reaction time is 12 h.

[0046] (5) Remove the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then place it in a vacuum drying oven at 80°C for 18 hours. After drying, the final product - nickel-based self-supporting water electrolysis hydrogen evolution catalyst - is obtained.

[0047] Phase analysis was performed on the porous nickel matrix prepared in this embodiment and the final product, a nickel-based self-supporting electrolytic hydrogen evolution catalyst for water splitting. The results are as follows: Figure 3 As shown. By Figure 3It can be seen that the XRD characteristic peak of the obtained porous nickel matrix corresponds to elemental nickel (PDF#04-0850), and the XRD characteristic peak of the nickel-based self-supporting electrolytic hydrogen evolution catalyst obtained after hydrothermal reaction corresponds to Ni3Se2 (PDF#19-0841). This proves that the main component of the nickel-based self-supporting electrolytic hydrogen evolution catalyst is Ni3Se2@Ni, with nickel metal contributing to the current collector and Ni3Se2 contributing to the catalytic activity.

[0048] The prepared nickel-based self-supported water electrolysis hydrogen evolution catalyst was used as the working electrode for water electrolysis hydrogen evolution, denoted as Ni3Se2@Porous Ni self-supported electrode. The microstructure of the Ni3Se2@Porous Ni self-supported electrode was characterized, and the results are as follows: Figure 4 As shown, the microstructure of the product consists of a large number of nanosheets vertically grown on a porous metal framework, completely covering the metal portion of the substrate.

[0049] Example 3: (1) Weigh 4g of 200-mesh nickel powder and select a graphite mold with a diameter of φ50; (2) The nickel powder is loaded into the graphite mold, and a graphite gasket is placed at the upper and lower ends of the graphite sleeve (i.e., between the graphite sleeve and the graphite conical top). The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve and smaller than the outer diameter of the graphite sleeve. (3) The graphite mold obtained in step (2) is placed in an SPS furnace for sintering. The sintering temperature is 800℃, the heating rate is 80℃ / min, and the sintering holding time is 2min. After sintering, the graphite mold is cooled to room temperature and removed to obtain a porous nickel matrix.

[0050] (4) Weigh 0.8 mmol of Na2SeO3 powder and dissolve it in 50 mL of distilled water. After stirring thoroughly, obtain solution A. Then, transfer solution A together with the porous nickel matrix obtained in step (3) into the polytetrafluoroethylene liner of a stainless steel hydrothermal reactor, seal the hydrothermal reactor, and place it in a drying oven for hydrothermal reaction. The hydrothermal reaction temperature is 190 °C, and the reaction time is 12 h.

[0051] (5) Remove the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then place it in a vacuum drying oven at 70°C for 24 hours. After drying, the final product - nickel-based self-supporting water electrolysis hydrogen evolution catalyst - is obtained.

[0052] The nickel-based self-supporting water electrolysis hydrogen evolution catalyst prepared in this embodiment was characterized by SEM images, and the results are as follows: Figure 5 As shown. From Figure 5As can be seen, after the nickel-based self-supporting electrolytic hydrogen evolution catalyst prepared in this embodiment is magnified 5,000 times, it can be seen that the surface of the material has a pore structure with a pore size of about 2 μm. The catalytic active phase is uniformly grown in situ in the form of small plate-like particles on the porous nickel matrix, which lays the foundation for good catalytic activity and durability.

[0053] The prepared nickel-based self-supporting hydrogen evolution catalyst for water electrolysis was used as the working electrode for hydrogen evolution in water electrolysis, and was denoted as Ni3Se2@Porous Ni self-supporting electrode.

[0054] To test the electrocatalytic water splitting performance of the product prepared in this invention, an electrochemical workstation was used to conduct a three-electrode test experiment. The electrolyte used in this experiment was a 1 mol / L KOH solution. The obtained Ni3Se2@Porous Ni self-supporting electrode was directly used as the working electrode, a graphite rod was used as the counter electrode, and a calomel electrode was used as the reference electrode. To demonstrate the advantages of the porous nickel matrix in this invention, Ni3Se2 was loaded onto commercially available nickel foam (NF) using the same selenization process. That is, the porous nickel matrix was replaced with NF according to the preparation process in steps (4) and (5) of this embodiment, and the other steps were the same as in steps (4) and (5) of this embodiment, to obtain the Ni3Se2@NF self-supporting electrode. The durability of the Ni3Se2@NF electrode and the Ni3Se2@Porous Ni self-supporting electrode was tested by chronoamperometry (CA). The voltage was set to -1.4 V, and the results were obtained at 85 mA cm⁻¹. -2 The CA curves under current density are shown in the figure. Figure 6 As shown, the self-supporting electrode based on NF exhibited a 31% performance degradation in less than 50 hours, while the Ni3Se2@Porous Ni self-supporting electrode prepared in this embodiment only showed a 3% performance degradation after 220 hours, indicating that the material has excellent electrocatalytic hydrogen evolution activity and durability.

[0055] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. The present invention can also have other embodiments based on the above structure and function, which will not be listed hereafter. Therefore, any simple modifications, equivalent changes, and alterations made by those skilled in the art to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a nickel-based self-supporting hydrogen evolution catalyst for water electrolysis, characterized in that... Specifically, the following steps are included: (1) Weigh a certain amount of nickel powder and select a graphite mold of appropriate size according to the size of the final product required; (2) Load nickel powder into a graphite mold, and place a graphite gasket at the upper and lower ends of the graphite sleeve respectively. The inner diameter of the graphite gasket is larger than the diameter of the central hole of the graphite sleeve and smaller than the outer diameter of the graphite sleeve. (3) The graphite mold was placed in a spark plasma sintering furnace for sintering. After sintering, it was cooled to room temperature and removed to obtain a porous nickel matrix. (4) Weigh a certain amount of sodium selenite and dissolve it in distilled water. After stirring thoroughly, obtain solution A. Then transfer solution A and the porous nickel matrix obtained in step (3) into the polytetrafluoroethylene liner of the stainless steel hydrothermal reactor, seal the hydrothermal reactor, and place it in a drying oven for hydrothermal reaction. (5) Take out the porous nickel matrix after reaction from the polytetrafluoroethylene liner, rinse it three times with distilled water, then rinse it three times with alcohol, and then put it into a vacuum drying oven. After drying, the final product - nickel-based self-supporting electrolytic hydrogen evolution catalyst is obtained.

2. The preparation method of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 1, characterized in that: In step (1), the particle size of the nickel powder is 100~300 mesh.

3. The preparation method of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 1, characterized in that: In step (3), the sintering temperature is 600℃~1200℃, the heating rate is 50~100℃ / min, and the sintering holding time is 2min.

4. The preparation method of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 1, characterized in that: In step (4), the amount of sodium selenite used is 0.1~0.8 mmol, and the concentration of Na2SeO3 in solution A is 2~16 mmol / L.

5. The preparation method of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 1, characterized in that: In step (4), the hydrothermal reaction temperature is 180~200℃ and the reaction time is 6~12 h.

6. The preparation method of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 1, characterized in that: In step (5), the drying temperature of the vacuum drying oven is 60~80℃ and the drying time is 12~24 h.

7. The nickel-based self-supporting hydrogen evolution catalyst for water electrolysis prepared by the preparation method according to any one of claims 1 to 6.

8. The application of the nickel-based self-supporting electrolytic hydrogen evolution catalyst as described in claim 7 in the electrolytic hydrogen evolution reaction and oxygen evolution reaction of water under alkaline conditions.

Citation Information

Patent Citations

  • Porous nickel framework material and preparation method thereof

    CN108405848A

  • Graphite die for spark plasma sintering

    CN216325088U